Graphene oxide as a template for a complex functional oxide1. Issue 32 (28th August 2015) - Boston, R.; Bell, A.; Ting, V. P.; Rhead, A. T.; Nakayama, T.; Faul, C. F. J.; Hall, S. R.
<x xml:space="preserve">Abstract</x> Graphene oxide monoliths of defined macromorphology are used to direct the structure of complex oxides for improved functionality.